A Combined Phytochemistry and Network Pharmacology Approach to Reveal Potential Anti-NSCLC Effective Substances and Mechanisms in Marsdenia tenacissima (Roxb.) Moon (Stem) - Liu, Pei; Xu, Dong-Wei; Li, Run-Tian; Wang, Shao-Hui; Hu, Yan-Lan; Shi, Shao-Yu; Li, Jia-Yao; Huang, Yu-He; Kang, Li-Wei; Liu, Tong-Xiang (Frontiers in Pharmacology, 2021)
Marsdeniae tenacissimae Caulis is a traditional Chinese medicine Tongguanteng (TGT) that is often used for the adjuvant treatment of cancer. In our previous research, we found that the ethyl acetate extract of TGT inhibits the growth of lung adenocarcinoma A549 cells. To elucidate the anti-tumor effective substances and mechanism of action of TGT, we designed an approach that was aimed to isolate compounds, which was then followed by cytotoxicity screening, network pharmacology analysis, and cellular and molecular experiments. Nineteen constituents were isolated from the ethyl acetate extract of TGT. Two new steroidal saponins were quantified using ultra-performance liquid chromatography-photodiode array coupled with quadruple time-of-flight mass（UPLC-ESI-Q/TOF-MS）. Then, we screened these constituents for anti-NSCLC cell activity in vitro and obtained six target compounds. Furthermore, a compound-target-pathway network of six bioactive ingredients were constructed to identify the potential pathways that regulate its anticancer effects. A total of 205 putative targets associated with TGT and 270 putative targets related to NSCLC were derived from online databases and target prediction tools. Protein-protein interaction networks of drug and disease putative targets were constructed, and 18 candidate targets were identified based on topological features. Pathway enrichment analysis identified related pathways, including PI3K/AKT, VEGF, and EGFR tyrosine kinase inhibitor resistance, which are associated with reactive oxygen species (ROS) metabolic processes and intrinsic apoptotic pathways. Then, a series of cellular experiments was used to validate the drug-target mechanisms predicted by network pharmacology analysis. The experimental results showed the four C21 steroidal saponins could upregulate Bax and downregulate Bcl-2 expression, thereby changing the mitochondrial membrane potential, producing ROS, and releasing cytochrome C, which finally activates caspase-3 and -9 and as well as caspase-8 that induces apoptosis in A549 cells. At the same time, these also downregulate the expression of MMP-2 and MMP-9 proteins, further weakening their degradation of extracellular matrix components and type IV collagen and inhibiting the migration and invasion of A549 cells. In conclusion, our study provides knowledge on the chemical composition and anti-tumor mechanism of TGT, which may be exploited as a promising therapeutic option for lung cancer.